COMPARATIVE AND APPLIED LINGUISTICS: GLOBAL APPROACHES - Kamolova Sabrina Farxod qizi, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article discusses the importance of comparative and applied linguistics in modern language learning. It mainly focuses on how comparing languages, especially English and Uzbek, can help learners understand linguistic differences more clearly. In addition, the paper looks at practical aspects of language teaching, including language and technology and the use of modern technologies, also give brief information about historical development. It is argued that combining theory with practice makes language learning more effective and meaningful.